Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini) - Czerwiński, Tomasz; Szawaryn, Karol; Tomaszewska, Wioletta (European Journal of Taxonomy, 2020)
Three new Papuan species of the ladybird genus Rhyzobius Stephens, Rhyzobius albinos sp. nov., R. atramentarius sp. nov. and R. serratus sp. nov., are described, diagnosed and illustrated. An updated key to species of Rhyzobius from New Guinea is provided.